The Role of Using Modern Managerial Accounting Techniques in Reducing Production Costs in the Listed Industrial Companies on the Amman Stock Exchange - Turki Shatnawi, Belal Nayef; Taber, Thaer Abu (ExcelingTech, 2020)
Abstract This study aimed to identify the role of the use of modern administrative techniques in managerial accounting, which is the target cost technology and cost technology based on activities and quality cost technology, value engineering technology in reducing production costs in Jordanian industrial companies listed on the Amman Stock Exchange, as these technologies demonstrated its high ability to reduce costs in industrial companies and provide the necessary information to the higher departments to take appropriate decisions, which guaranteed these companies competing in the market and continuity. The study community consisted of the 56 public joint-stock industrial companies listed on the Amman Stock Exchange as it is in the year 2020, and to achieve the objectives of the study, the researcher developed the study instrument represented in preparing the questionnaire and distributed it to the sample of the study which represented the financial managers, production managers, marketing managers, cost managers and accountants In the public joint-stock industrial companies listed on the Amman Stock Exchange, to obtain the results of the study, the researcher used the descriptive statistical method to study the characteristics of respondents using frequencies and percentages through the use of the Statistical Packages Program for Social and Economic Sciences (SPSS). Among the most important findings of the researchers, there are differences related to statistical significance in the role of using modern accounting techniques in reducing production costs in public joint-stock industrial companies provided on the Amman Stock Exchange, and that public joint-stock industrial companies seek to reduce production costs at an early stage of production. Based on the results of this study, the researcher recommended several recommendations, the most important of which is the continuous development of general industrial companies in the Amman Stock Exchange for modern managerial accounting technique.